Customer intention to commit motor insurance fraud: a literature review - Nurul Hidayah Mohd Yusof (Universiti Pendidikan Sultan Idris, 2018)
Customer intention to commit motor insurance fraud: a literature review by Nurul Hidayah Mohd Yusof